2016
DOI: 10.4238/gmr.15017409
|View full text |Cite
|
Sign up to set email alerts
|

Antisense expression of Gossypium hirsutum UDP-glucuronate decarboxylase in Arabidopsis leads to changes in cell wall components

Abstract: ABSTRACT. UDP-glucuronate decarboxylase (UDP-xylose synthase; UXS, EC 4.1.1.35) is an essential enzyme of the non-cellulosic polysaccharide biosynthetic pathway. In the present study, using transient expression of fluorescently labeled Gossypium hirsutum UXS (GhUXS3) protein in onion epidermal cells, we observed that this protein was distributed in the cytoplasm. The GhUXS3 cDNA of cotton was expressed in an antisense orientation in Arabidopsis thaliana by Agrobacterium tumefaciensmediated transformation. Homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Our results found that almost all DEGs of three carbohydrate metabolism pathways ("starch and sucrose metabolism", "galactose metabolism" and "pentose and glucuronate interconversions") were up-regulated in "T3 vs R" and "T4 vs H", and these DEGs were related to xylose, glucose, and galactose metabolism. For example, The UXS genes which were up-regulated here were positive regulators of xylose, glucose, and galactose in tobacco or Arabidopsis by the RNAi transgenic experiments [28,29]. These genes' up-regulation indicated the activation of the production of xylose, galactose and glucose related metabolites.…”
Section: Discussionmentioning
confidence: 82%
“…Our results found that almost all DEGs of three carbohydrate metabolism pathways ("starch and sucrose metabolism", "galactose metabolism" and "pentose and glucuronate interconversions") were up-regulated in "T3 vs R" and "T4 vs H", and these DEGs were related to xylose, glucose, and galactose metabolism. For example, The UXS genes which were up-regulated here were positive regulators of xylose, glucose, and galactose in tobacco or Arabidopsis by the RNAi transgenic experiments [28,29]. These genes' up-regulation indicated the activation of the production of xylose, galactose and glucose related metabolites.…”
Section: Discussionmentioning
confidence: 82%
“…Due to the different prediction method, there were considerable discrepancy, but the AtUXSs in cytoplasm were ties specific function. Similar to AtUXS genes, antisense-expressed GhUXS3 gene, which was located in cytoplasm, could reduce xylose content in stem in Arabidopsis [14]. GhD08G085500 and GhD12G134200, predicted in cytoplasm, had higher expression.…”
Section: Discussionmentioning
confidence: 94%
“…Also, rice and populous genes were cloned [11,12]. In G. hirsutum, three GhUXS genes expression suggests UXS may play important roles in cotton fiber development [13,14].…”
Section: Introductionmentioning
confidence: 99%